DIPLOMASI EKONOMI AMERIKA SERIKAT TERHADAP JEPANG TENTANG EKSPOR DAGING SAPI PERIODE 2017-2020 - Andrea Gladys Gabriella, (2022)
The United States (US) is one of the beef exporting countries in Japan. Japan has a high level of beef demand but this advantage was followed by a decrease in the volume of beef exports in 2017-2020 due to export barriers faced by the US. So, this study aims to discuss the efforts made by the US in resolving trade barriers regarding beef exports in Japan using the concept of economic diplomacy and international trade theory. The method used in this study is descriptive qualitative. Sources of data in the form of primary data and secondary data. Data collection techniques used are from interviews and documentation studies. This study also uses the stages of analysis according to Miles, Huberman, and Saldana, namely data condensation, data display, also drawing and verifying conclusions. The final results obtained through this study indicate that as an effort by the US to remove the trade barriers it faces in its beef exports to Japan, the US makes efforts through economic diplomacy. Economic diplomacy efforts carried out by the US are through the establishment of bilateral trade agreements with Japan through the US-Japan Trade Agreement (USJTA) and the promotion of beef in Japan. Through these efforts, the US succeeded in lowering its beef import tariffs in Japan, adjusting the beef safeguard mechanism in Japan, and bridging US businesses with consumers in Japan. In carrying out its economic diplomacy efforts, there are various actors involved, such as the United States Trade Representatives, the United States Department of Agriculture, and NGOs. Economic diplomacy efforts carried out by the US succeeded in increasing US beef exports after the establishment of the USJTA was implemented on January 1, 2020.